Recent Advances and Future Perspectives in Cotton Research - Huang, Gai; Huang, Jin-Quan; Chen, Xiao-Ya; Zhu, Yu-Xian (Annual review of plant biology, 2021)
Cotton is not only the world's most important natural fiber crop, but it is also an ideal system in which to study genome evolution, polyploidization, and cell elongation. With the assembly of five different cotton genomes, a cotton-specific whole-genome duplication with an allopolyploidization process that combined the A- and D-genomes became evident. All existing A-genomes seemed to originate from the A -genome as a common ancestor, and several transposable element bursts contributed to A-genome size expansion and speciation. The ethylene production pathway is shown to regulate fiber elongation. A tip-biased diffuse growth mode and several regulatory mechanisms, including plant hormones, transcription factors, and epigenetic modifications, are involved in fiber development. Finally, we describe the involvement of the gossypol biosynthetic pathway in the manipulation of herbivorous insects, the role of in gland formation, and host-induced gene silencing for pest and disease control. These new genes, modules, and pathways will accelerate the genetic improvement of cotton. Expected final online publication date for the , Volume 72 is May 2021. Please see http://www.annualreviews.org/page/journal/pubdates for revised estimates.